Correlation of Perkins Hand-Held Applanation Tonometer with Non-Contact Tonometer (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: To correlate the IOP by the use of Perkins hand-held applanation tonometer (PAT) with Non-contacttonometer (NCT). Materials & Methods: Prospective cross-sectional study done on 148 eyes & 3 readingswere taken for each method & mean calculated. Statistical analysis: Unpaired-T test & Correlation-coefficient, Sensitivity & Specificity were calculated for the NCT. Results: Mean age of subjects was 56.01±9.73 yrs. Mean IOP with PAT & NCT 15.43 mmHg (95% CI 15.14–15.76) & 15.13 mmHg (95% CI 14.81–15.46) respectively. NCT shows excellent agreement with PAT. Correlation coefficient(r) of IOP measuredby NCT & PAT is 0.97 & 0.91 for RE & LE respectively with p value <0.05, showed strong positivecorrelation between the IOP measured by NCT & PAT. The NCT showed high sensitivity 86% & highspecificity 97.9 % respectively, coming across an excellent agreement with PAT. Interpretation: NCT iseasy to operate (non medical & Paramedical staff), minimum risk of infection & without any observer bias.Only drawback is the cost. Conclusion: The current study shows that the NCT compares well with the PAT.The NCT can be used as a reliable screening tool.